2021
DOI: 10.1007/s40291-021-00553-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Two Molecular Tools for Diagnosis of Congenital Chagas Disease

Abstract: Background and Objective The real prevalence of congenital Chagas disease is undefined because of difficulties in the detection of Trypanosoma cruzi by microscopic examination. The aim of this study was to determine the diagnostic accuracy of two molecular diagnostic tools, qPCR and LAMP, in the diagnosis of congenital Chagas disease in a clinical setting. Methods To this end, we conducted a prospective cohort study in a tertiary care center, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The studies also included information on the type of sample collected from the patients (in all cases, these were blood samples) and the number of samples taken. The blood volume taken ranged from 0.5 mL [15,19] to 15 mL [5]; 22 of the 32 (68.7%) studies indicated the preservation conditions of the samples; none reported the time period between sample collection and extraction or performance of the diagnostic tests. A total of 6 studies (18.7%) did not specify the type of ampli cation control of the tests analysed.…”
Section: Qualitative Synthesis: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies also included information on the type of sample collected from the patients (in all cases, these were blood samples) and the number of samples taken. The blood volume taken ranged from 0.5 mL [15,19] to 15 mL [5]; 22 of the 32 (68.7%) studies indicated the preservation conditions of the samples; none reported the time period between sample collection and extraction or performance of the diagnostic tests. A total of 6 studies (18.7%) did not specify the type of ampli cation control of the tests analysed.…”
Section: Qualitative Synthesis: Results Of Individual Studiesmentioning
confidence: 99%
“…Some individual ndings, such as those of the qPCR method, are more reliable than cPCR for CD diagnosis (Cura et al [19]); the commercial qPCR kit is more e cient in congenital Chagas disease diagnosis (Benatar et al [13]); the kDNA OligoC-TesT showed a signi cantly higher sensitivity than satDNA OligoC-TesT (De Winner et al [20] and Ramírez et al [35]); and the Tc24-based PCR assay is more sensitive than that based on kDNA (Espinoza et al [24]) or TcH2AF/R PCR (Gil et al [26]). In addition, LAMP kits offer appropriate analytical sensitivity for the diagnosis of CD patients and are potentially useful for monitoring treatment response (Besuschio et al, 2017 and2020 [7, 14]); they also offer high performance for the diagnosis of congenital CD (Bisio et al [15], Flores-Chavez et al…”
Section: Qualitative Synthesis: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations